GAMBARAN PENDAPATAN, PENGETAHUAN DAN POLA ASUH IBUSERTA STATUS GIZI ANAK BALITA DI WILAYAH KERJA PUSKESMAS SIBUHUAN KABUPATEN PADANG LAWAS TAHUN 2017 - Sri Masitoh Hasibuah; Evawany Y Aritonang; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
At present, Indonesia faces multiple nutritional problems that are less nutritional problems and more nutritional problems. The problem of malnutrition is generally caused by poverty, lack of food availability, poor quality of environment, lack of knowledge of society, on the other hand nutritional problem is more caused by economic progress in certain society layer accompanied. The results of Riskesdas (2013) nationally estimated the prevalence of malnourished children under five and less by 19.6%. Number of 23,708,844 children, so the number of malnutrition and less equal to 4,646,933 children under five.The results of the preliminary survey in the work area of Sibuhuan Health Center with the number of children under five years of age 1,536 people. showed that nutritional status of BB/U malnutritional 2.60%, TB/U short 1.82% and BB/TB lean 2.27%. The purpose of this study is to know the description of income, knowledge and parenting patterns of mother and nutritional status of children under five in the working area of Sibuhuan Public Health Center in Padang Lawas year 2017. Type research is a descriptive survey with cross sectional research design. The population in this study was all childrens aged under 12-59 months with a sample of 94 people.                The result of the research showed that the nutritional status of children based on the weight of the nutritional status with malnutrition status category and less was 58,6%, chronic malnutrition (TB / U) with short and short nutritional status category 55,3%, while the nutritional status of chronic (BB / TB) with the category of nutritional status is very thin and thin 47,8%, more income in the category of income below the UMK (<Rp 1.605.000) as much as 55,3%, more knowledge in 40,4% enough category, mother in feeding more on category not good 55,3% and care of children under five more in good category 56,4%, then mother care pattern (feeding and care of children under five) more in category not good 52,1% while good 47,9%.  It is recommended that Padang Lawas District Health Office, Sibuhuan Health Center and health workers are expected to increase counseling, supervision and more active in handling nutritional status of children under five so that better nutrition of children under five and increasing of public health status. Mothers are expected to pay more attention and improve children nutritional status toddler. Keywords: Nutritional Status Of Children Under Five, Income, Knowledge And Parenting Patterns Of Mother